Efficacy of Sub-Tenon Micro-Perfusion of Cyclophosphamide in Rabbits with Severe Ocular Inflammation - Zhao L; Peng M; Lin W; Tan Q; Khan MA; Lin D (Dove Medical Press, 2020)
Libei Zhao, Manqiang Peng, Wenxiang Lin, Qian Tan, Muhammad Ahmad Khan, Ding Lin Department of Ophthalmology, Changsha Aier Eye Hospital, Aier School of Ophthalmology, Central South University, Changsha, People’s Republic of ChinaCorrespondence: Ding LinDepartment of Ophthalmology, Changsha Aier Eye Hospital, Aier School of Ophthalmology, Central South University, No. 388, Section 2, Furong Middle Road, Changsha City, Hunan Province 410005, People’s Republic of ChinaTel +86 13787255158Email linding@csu.edu.cnPurpose: To explore the feasibility of cyclophosphamide (CP) via a sub-Tenon micro-perfusion system (SMS) in rabbits, and assess its therapeutic efficacy in severe ocular inflammation.Materials and Methods: Distribution and pharmacokinetics of CP were evaluated in vivo, and the concentrations of CP in plasma, vitreous humor, and retina/choroid were quantitated by ultra-high-performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS) at different time points. After induction of severe experimental uveitis, rabbits were divided into three groups (n=8 in each): the SMS group, subconjunctival injection (SI) group, and control group. Clinical inflammatory score was assessed in rabbits. Electroretinography and histopathology were performed on post-treatment day 8. Statistical analyses were performed using Mann–Whitney and Kruskal–Wallis tests. P-value less than 0.05 was considered significant.Results: The concentrations of CP in vitreous humor and retina/choroid in the SMS group were significantly higher than that of the SI group at 3, 6, 10, and 24 hours (P< 0.01), while plasmatic CP concentrations were comparable at all time points in the SMS group and SI group (P> 0.05). The SMS group showed significantly less inflammation compared to the control group and SI group. Furthermore, the restoration of retinal structure and function were more obvious in the SMS group compared with conventional SI application.Conclusion: Sub-Tenon micro-perfusion of CP exhibited satisfied therapeutic efficacy in rabbits with severe ocular inflammation and may provide a promising alternative for controlling ocular inflammatory disease and immune-mediated ocular diseases.Keywords: cyclophosphamide, sub-Tenon drug delivery, ocular inflammation, treatment, rabbit